Psychological risk factors and cardiovascular disease - Carola, Valeria; Vincenzo, Cristina; Di Vincenzo, Giulia; Morale, Chiara; Cecchi, Valentina; Nicolais, Giampaolo (Frontiers in Psychology, 2024)
Objectives: Cardiovascular diseases (CVDs) are a leading cause of death worldwide, emerging from a combination of several factors. The aim of this review is to define the psychological factors that are significant in the development and progression of these disorders. Methods: Studies published through 2023 concerning adults with psychological vulnerability factors and/or cardiovascular disease were selected through searches of PubMed, PsychINFO, Science Direct, and Google Scholar. Results: Psychological stress may influence CVD in combination with other risk factors, or it can act independently, as in cases of workplace stress, post-traumatic stress disorder, Takotsubo syndrome, and bereavement. Coping strategies, anxiety, and depression have also been identified as relevant psychological factors in cardiac patients. Adverse childhood experiences are linked to a reduced quality of life and have been identified as significant risk factors for the development of acquired cardiovascular disease. Conclusions: This review demonstrates that several psychological factors affect cardiovascular function. An in-depth study of the psychological correlates of cardiovascular disorders would allow healthcare professionals to design more effective prevention and intervention programs.